2018
DOI: 10.1186/s12964-018-0251-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 facilitates muscle regeneration through modulation of fibro/adipogenic progenitors

Abstract: BackgroundChronic muscle injury is characteristics of fatty infiltration and fibrosis. Recently, fibro/adipogenic progenitors (FAPs) were found to be indispensable for muscular regeneration while were also responsible for fibrosis and fatty infiltration in muscle injury. Many myokines have been proven to regulate the adipose or cell proliferation. Because the fate of FAPs is largely dependent on microenvironment and the regulation of myokines on FAPs is still unclear. We screened the potential myokines and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 43 publications
(57 reference statements)
5
72
0
Order By: Relevance
“…In addition, our study found significantly more adipogenesis and increased FAP percentage in SS compared with TA after the same glycerol‐induced injury of each muscle. Kang et al found that the adipocyte area increased to approximately 6% in mouse TA muscle 7 days after glycerol injection using triple the dose used in our study. Lukjanenko et al showed similar results as our study regarding TA FI with approximately 1% adipocyte area at 2 weeks using a comparable glycerol dose.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, our study found significantly more adipogenesis and increased FAP percentage in SS compared with TA after the same glycerol‐induced injury of each muscle. Kang et al found that the adipocyte area increased to approximately 6% in mouse TA muscle 7 days after glycerol injection using triple the dose used in our study. Lukjanenko et al showed similar results as our study regarding TA FI with approximately 1% adipocyte area at 2 weeks using a comparable glycerol dose.…”
Section: Discussionsupporting
confidence: 52%
“…Intramuscular glycerol injection has been shown to induce muscle FI as an established model of muscle injury . To assess for differences in adipogenic and proliferative potential of FAPs in vivo across muscle groups after same FI‐inducing injury, 30 µl of 50% glycerol in 0.9% saline was injected into the mid‐bellies of the SS and tibialis anterior muscles, respectively, in a third group of PDGFRα‐eGFP reporter mice ( n = 4 per subgroup).…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic stress has been linked to FAP accumulation and fibro/adipogenic differentiation (Dammone et al, 2018;Gorski et al, 2018;Kang et al, 2018;Buras et al, 2019). Using several different genetic and diet-induced mouse models of diabetes, Mogi et al (2016) demonstrated that ectopic adipocyte accumulation in skeletal muscle was derived from PDGFRα + progenitors.…”
Section: Fibro/adipogenic Progenitors As the Cellular Source Of Intermentioning
confidence: 99%
“…For instance, by inhibiting TGF‐β1, FAPs were shown to become apoptotic in the presence of macrophages, which correlated with decreased fibrosis in vivo . Cytokines such as IL‐4 and IL‐15 were shown to prevent FAPs from undergoing adipogenic differentiation . Future studies should focus on elucidating the diverse differentiation mechanisms of FAPs.…”
Section: Stem Cells For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…101 Cytokines such as IL-4 and IL-15 were shown to prevent FAPs from undergoing adipogenic differentiation. 102,103 Future studies should focus on elucidating the diverse differentiation mechanisms of FAPs. Identification of precise factors and molecules that can modulate FAP activity to promote myogenic regeneration without fibrotic and fatty tissue deposition are likely to offer great therapeutic benefits to aging, diseased, or severely injured skeletal muscle.…”
Section: Fibro/adipogenic Progenitorsmentioning
confidence: 99%